2021
DOI: 10.1038/s41598-021-99930-5
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin-E2 receptor-4 stimulant rescues cardiac malfunction during myocarditis and protects the heart from adverse ventricular remodeling after myocarditis

Abstract: Cardioprotective effect of prostaglandin-E2 receptor-4 (EP4) stimulation on the ischemic heart has been demonstrated. Its effect on the heart affected by myocarditis, however, remains uncertain. In this study, we investigated therapeutic effect of EP4 stimulant using a mouse model of autoimmune myocarditis (EAM) that progresses to dilated cardiomyopathy (DCM). EP4 was present in the hearts of EAM mice. Treatment with EP4 agonist (ONO-0260164: 20 mg/kg/day) improved an impaired left ventricular (LV) contractili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This suggests that Akt signaling underlies the cardioprotective mechanism of the PGE 2 /EP 4 system in I/R. Additionally, several studies demonstrated the utility of EP 4 as a promising therapeutic target in cardiac diseases including not only ischemic heart disease but also inflammatory heart disease [ 34 ] and cardiac hypertrophy [ 35 ]. Further investigations are necessary to extend the clinical benefits of EP 4 agonists in cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Akt signaling underlies the cardioprotective mechanism of the PGE 2 /EP 4 system in I/R. Additionally, several studies demonstrated the utility of EP 4 as a promising therapeutic target in cardiac diseases including not only ischemic heart disease but also inflammatory heart disease [ 34 ] and cardiac hypertrophy [ 35 ]. Further investigations are necessary to extend the clinical benefits of EP 4 agonists in cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…158 An EPr4 agonist reduces myocardial fibrosis in response to pressure overload 159 and reduces myocardial fibrosis, hypertrophy, and inflammation after myocarditis. 160,161 PGE 2 also regulates cardiac contractility: it reduces cardiac contractility via the EPr3 receptor 162 and increases it via the EPr4 receptor. 162 PGE 2 may also play a role in cardiac regeneration.…”
Section: Pge 2 In Myocardial Remodelingmentioning
confidence: 99%
“…158 An EPr4 agonist reduces myocardial fibrosis in response to pressure overload 159 and reduces myocardial fibrosis, hypertrophy, and inflammation after myocarditis. 160,161…”
Section: Pge2 In Myocardial Remodelingmentioning
confidence: 99%
“…Furthermore, the beneficial effects ascribed to the BPC 157’s muscle healing and muscle function recovery, might have a very wide range (for review, see [ 1 , 3 , 4 , 5 , 6 , 8 , 9 , 32 , 33 , 34 , 92 ]). In its full extent, the range of BPC 157 therapy and its huge curing potential as a “treatment” (for review, see [ 1 , 3 , 4 , 5 , 6 , 8 , 9 , 32 , 33 , 34 , 92 ]) might largely override the range of the beneficial effects commonly reported with standard cytoprotective agents (for review, see [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]) (i.e., prostaglandins’ beneficial effects on the stomach [ 35 ], intestine [ 38 ], liver [ 130 ], pancreas [ 39 ], kidney [ 38 , 131 ], and heart [ 132 ]). Likewise, its easy applicability during the course of an injury’s treatment might bypass the limitation of the standard agents (for review, see [ 1 , 3 , 4 , 5 , 6 , 8 , 9 , 32 , 33 ,…”
Section: Muscle Healingmentioning
confidence: 99%